МАХТУМҚУЛИНИНГ БАЪЗИ ЎЗБЕКЧА ШЕЪРЛАРИ ТАРЖИМАСИДА ВАЗННИНГ АҲАМИЯТИ - Сапаева, Ф. (FAN va JAMIYAT, 2018)
In the article the genre structure of Maktumkuli‘s poems and their Uzbek translations are studied from the point of view of meters. His poems were translated inti Uzbek by Uzbek translators M.Shayhzoda, J.Sharipov, E.Ochilov, M.Ahmad, M.Azim, O.Safarov. Their works are considered as the object of the research. Samples of analyses were discussed in the Uzbek and Turkmen languages.